Statement on Management of Children with Allergic Diseases During New Coronaviral Infection SARS-CoV-2 Pandemic (COVID-19 Infection) - Alexander A. Baranov; Leyla S. Namazova-Baranova; Rakhim M. Khaitov; Elena A. Vishneva; Natalia I. Il'ina; Natalia M. Nenasheva; Tatiana V. Kulichenko; Daria S. Fomina (Педиатрическая фармакология)
The COVID-19 infection caused by the new coronavirus SARS-CoV-2 has become the real pandemic. Children account for 1–6% of all diagnosed COVID-19 cases. Generally, children have mild disease in comparison to adults, and their mortality rates are extremely low. Despite the fact that all the main efforts of the medical and political community are now focused on preventing the pandemic spread and organizing medical care for patients with moderate and severe COVID-19 course, we still have to remember to implement adequate help for patients with chronic diseases, especially for children with allergic diseases. The pandemic period coincided with natural weather period of dusting of causative plants, that led to annual escalation of both allergic rhinitis and asthma in patient group with specific sensitization to tree pollen. Leading experts of allergology (adapting to modern conditions) have created key guidelines on management of children with allergic diseases during the COVID-19 pandemic. These guidelines are based on the data and results from the Union of Pediatricians of Russia, Russian Association of Allergologists and Clinical Immunologists, European Academy of Allergy and Clinical Immunology (EAACI), European Respiratory Society (ERS), American Thoracic Society (ATS), Global Strategy for Asthma Management (GINA), Initiative on Allergic Rhinitis and its Impact on Asthma (ARIA/MACVIA).